The art of public speaking - Lucas, Stephen (McGraw-Hill, 2004)
Lucas' The Art of Public Speaking is the leading public speaking textbook in the field. Whether a novice or an experienced speaker when beginning the course, every student will learn how to be a better public speaker through Lucas' clear explanations. Creative activities, vivid examples, annotated speech samples, and foundation of classic and contemporary rhetoric provide students a strong understanding of public speaking.